Case report: A novel CASK mutation in a Chinese female child with microcephaly with pontine and cerebellar hypoplasia - Xie, Guilan; Zhang, Yan; Yang, Wenfang; Yang, Liren; Wang, Ruiqi; Xu, Mengmeng; Sun, Landi; Zhang, Boxing; Cui, Xiaoyi (Frontiers in Genetics, 2022)
Objective: Microcephaly with pontine and cerebellar hypoplasia (MICPCH) is a rare X-linked dominant genetic disease, and most MICPCHs are ascribed to CASK mutations, while few are revealed in Chinese patients. This study aims to identify the pathogenic mutation in a Chinese proband with MICPCH. Methods: A 3-year-old female Chinese proband with MICPCH and her parents were included. Clinical data were collected from the medical records and recalled by the proband’s mother. Whole genome sequencing and Sanger sequencing were used to find the pathogenic mutation of MICPCH. Results: The proband presented with postnatal progressive microcephaly, cerebellar hypoplasia, intellectual disability, motor and language development retardation and limb hypertonia. Genetic analysis indicated that there was a novel compound heterozygote nonsynonymous mutation, c.755T>C(p.Leu252Pro) in exon8 of CASK gene in the proband, but not in her parents. This CASK mutation has not been reported in other databases. Conclusion: This study broadens the mutation spectrum of the CASK gene and is of great value for precise prenatal diagnosis and genetic counseling.